Redefining those subtle borders: transhumanism, frontiers, retroprogression and hermeneutics at the crossroads of teaching - Francisco Carrera, Francisco José (Frontiers in Education, 2024)
The field of education is undergoing significant transformations, which implies that valuable views from the past may be completely overlooked in the rapid progress we are experiencing. Transhumanism, as a prevailing ideology, appears to imply an advancement at an ever-increasing speed. An interesting prospect would be to reflect on transhumanism in relation to retroprogression and phronesis to understand how limitations operate within the realm of education. Interpretation, therefore, becomes one of the fundamental tools for educators in this highly complex environment. Their role as meta-interpreters can be founded in a return to hermeneutics as both an art and a science. By doing this, the past and future can be harmonized in the present, with the transhumanist principles maintaining the human element. In conclusion, education will continue to be an act of human understanding that necessitates complete attention and presence of educators, who are, therefore, able to offer meaningful actions by properly understanding the here and now and the uniqueness of every teaching situation.